2017
DOI: 10.1159/000480510
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Thai Parkinson's Disease Screening Tool and the Prevalence of Parkinsonism and Parkinson's Disease, Based on a Community Survey in Bangkok

Abstract: Introduction: Few epidemiological data of parkinsonism and Parkinson's disease (PD) exist in Southeast Asia. We aimed to develop and validate a screening tool, and investigate the prevalence of parkinsonism and PD via a community survey. Methods: A PD-screening tool comprising 11 “yes/no” items was developed in a clinical setting and validated in the community. The prevalence of PD and parkinsonism was investigated in a survey that included PD screening tools, face-to-face interviews, and physical examinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Symptoms and signs previously considered in PD and parkinsonism screening questionnaires from previous community and hospital-based PD screening questionnaire development studies were also comprehensively reviewed ( 109–112 ). The Panel then reached a consensus on those items that were likely to indicate the presence of prodromal PD most strongly ( 63 , 64 , 109 , 111 , 113 , 114 ).…”
Section: Methods and Analysismentioning
confidence: 99%
“…Symptoms and signs previously considered in PD and parkinsonism screening questionnaires from previous community and hospital-based PD screening questionnaire development studies were also comprehensively reviewed ( 109–112 ). The Panel then reached a consensus on those items that were likely to indicate the presence of prodromal PD most strongly ( 63 , 64 , 109 , 111 , 113 , 114 ).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The prevalence increases to 1.4% in individuals over 60 years of age and rises to 4.33% in those over 85 years of age (Keus et al., 2014). In Thailand, a prevalence of 706 PD patients per 100,000 population has been reported, which is 0.7% below the global average (Muangpaisan et al., 2017). The pathological hallmark of the disease occurs in the substantia nigra region of the brain, particularly in the substantia nigra pars compacta (SNc).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence is approximately 1% in US residents aged 60 years old and is expected to double in the next 10–20 years . A population‐based survey in a Thai community revealed that underdiagnosis of PD was common and that the age‐specific prevalence of PD was 706 per 100 000 population in those over 50 years of age . PD manifests with classic motor symptoms as well as non‐motor symptoms such as cognitive impairment and dementia.…”
Section: Introductionmentioning
confidence: 99%